2015
DOI: 10.1590/2176-9451.20.4.063-067.oar
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of facial morphology and sagittal relationship between dental arches in primary and mixed dentition

Abstract: OBJECTIVE: To assess facial morphology (Pattern) and sagittal relationship between dental arches (Class), and establish a potential association between them and the variables sex, age and ethnicity, among schoolchildren aged between 4 and 9 years old (mean age of 6.7 years) in primary and mixed dentitions. METHODS: The sample comprised 875 children (457 males and 418 females) attending schools in Descalvado, São Paulo, Brazil. An attempt was made with a view to establish a potential association between childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
1
7
0
2
Order By: Relevance
“…The mean interpremolar, intermolar dental and interpremolar, intermolar alveolar arch width in both maxillary and mandibular arches were found to be highest in hypodivergent patients and least in hyperdivergent patients, which was not found to be statistically significant. This is in conformance with the researches done by Uysal et al (2005), 15 Khera et al (2012), 8 Ribeiro et al (2012), 19 Grippaudo et al (2013), 20 Bhutta et al (2013), 1 Shahroudi and Etezadi (2013), 21 Prasad et al (2013), 22 Bălan et al (2014), 23 Nayer et al (2015), 24 Traldi et al (2015), 25 Gupta and Makhija (2016), 26 Perez et al (2016), 27 Aditi et al (2017), 28 and Nagrajmurthy (2017). 29 However, the data from this study presented an antithetical fashion between SN-MP angle and dental arch widths, the relationship was less strong, which showed that the SN-MP angle might not be only one of the contributing factors.…”
Section: Discussionsupporting
confidence: 79%
“…The mean interpremolar, intermolar dental and interpremolar, intermolar alveolar arch width in both maxillary and mandibular arches were found to be highest in hypodivergent patients and least in hyperdivergent patients, which was not found to be statistically significant. This is in conformance with the researches done by Uysal et al (2005), 15 Khera et al (2012), 8 Ribeiro et al (2012), 19 Grippaudo et al (2013), 20 Bhutta et al (2013), 1 Shahroudi and Etezadi (2013), 21 Prasad et al (2013), 22 Bălan et al (2014), 23 Nayer et al (2015), 24 Traldi et al (2015), 25 Gupta and Makhija (2016), 26 Perez et al (2016), 27 Aditi et al (2017), 28 and Nagrajmurthy (2017). 29 However, the data from this study presented an antithetical fashion between SN-MP angle and dental arch widths, the relationship was less strong, which showed that the SN-MP angle might not be only one of the contributing factors.…”
Section: Discussionsupporting
confidence: 79%
“…[ 21 ] A reliable diagnosis of the anteroposterior relationship between the dental arches may be made when complete primary dentition is achieved. [ 22 ] The range of postural alterations that can be readily compensated is greater in healthy individuals than in patients with occlusal problems. [ 14 ] Currently, most published data in this field refer to the effects of dental occlusion on head and body posture, [ 23 25 ] and very little information is available on the inverse effects of posture on malocclusion.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, these authors observed no association between ethnicity and dental arches. [ 22 ] However, another study reported that 60% of whites presented Class I malocclusion. [ 32 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diferente do que foi encontrado em estudo realizado em outro estado 23 , que apresentou, nos seus resultados, uma predominância do padrão facial tipo I (reto) em uma amostra constituída por 875 crianças, com idade média de 6,7 anos, em relação ao perfil facial, no presente estudo, foi constatado perfil convexo para a maioria da amostra (84,88%). Este fato deve ser levado em consideração, uma vez que a maioria dos indivíduos apresenta um perfil convexo ao nascimento e tem o padrão estabelecido definitivamente perto do surto puberal.…”
Section: Discussionunclassified